2003
DOI: 10.5702/massspec.51.196
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmentation of Amine Cluster Ion Including HCl. Proton Affinities of Drugs of Abuse.

Abstract: The fragmentation of the cluster ion, [A1῎HCl῎A2῎H] ῌ of amine bases A1 and A2, is studied by the BEBE type tandem mass spectrometer. The cluster ion, [A1῎HCl῎A2῎H] ῌ , is generated by the fast atom bombardment (FAB) ionization of mixture of two hydrochlorides of amines. The precursor ion is selected by the first analyzer (BE) and the product ions are scanned by the second analyzer (B/E linked scanning). ῌ are found to be related to their relative proton a$nities and are used to determine the proton a$niti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…With the compound set and experimental conditions shown in Figure , 10 out of 70 compounds were depleted by 20-fold or greater when using the 2-propanol modifier. However, analytes with higher proton affinities such as leucine (∼917 kJ/mol) and ephedrine (>965 kJ/mol) were not significantly affected by the addition of 2-propanol (∼798 kJ/mol) to the transport gas flow. , For the negative ion mode experimental conditions shown in Figure , 2-propanol did not significantly affect the ion intensities.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…With the compound set and experimental conditions shown in Figure , 10 out of 70 compounds were depleted by 20-fold or greater when using the 2-propanol modifier. However, analytes with higher proton affinities such as leucine (∼917 kJ/mol) and ephedrine (>965 kJ/mol) were not significantly affected by the addition of 2-propanol (∼798 kJ/mol) to the transport gas flow. , For the negative ion mode experimental conditions shown in Figure , 2-propanol did not significantly affect the ion intensities.…”
Section: Resultsmentioning
confidence: 88%
“…However, analytes with higher proton affinities such as leucine (∼917 kJ/mol) and ephedrine (>965 kJ/mol) were not significantly affected by the addition of 2-propanol (∼798 kJ/mol) to the transport gas flow. 18,19 For the negative ion mode experimental conditions shown in Figure 2, 2-propanol did not significantly affect the ion intensities.…”
Section: Figurementioning
confidence: 93%
“…The homemade He-DBDI seems as an atmospheric pressure chemical ionization (APCI) because of formation of hydronium ion, H 3 O + , in the positive mode of operation (Habib et al, 2014 , 2020 ). In addition, the proton affinity (PA) of this group of compounds is quite high i.e., PA for MA is 965 kJ/mol, and follows the increasing order: AM < MDA < MA < MDMA (Matsumura et al, 2003 ). Thus, these compounds efficiently form their protonated molecular ion, [M+H] + , in the positive ion mode.…”
Section: Headspace-dielectrictric Barrier Discharge (Dbd) Ionization-mentioning
confidence: 99%
“…Thus, molecules having high proton affinity were preferentially ionized. Matsumura et al demonstrated the order of the proton affinity of three illicit drugs: amphetamine < methamphetamine (965 kJ/mol) < MDMA . The proton affinity of a tertiary amine is generally higher than that of a primary amine, implying that that of cocaine is higher than that of MDMA.…”
Section: Resultsmentioning
confidence: 99%
“…Matsumura et al demonstrated the order of the proton affinity of three illicit drugs: amphetamine < methamphetamine (965 kJ/mol) < MDMA. 34 The proton affinity of a tertiary amine is generally higher than that of a primary amine, implying that that of cocaine is higher than that of MDMA. The vapor pressure of sample molecules is also an important factor in analyses using the headspace method.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%